MODUL PEMURIDAN MATE TERHADAP PERUBAHAN KARAKTER ANAK MUDA - Hannah Kenanga Eunike (STT Kristus Alfa Omega, 2019)
Christian Transformation showed by their character. Most of young people character transformation influenced by others too as such as families, education, friends, and media. Mate discipleship made by Beth-El Tabernakel Kristus Alfa Omega Gajahmada Semarang Church tried to help young people transfom their character to be Christlikeness. This research used quantitative reseacrh with a type of correlation descriptive research with the subject were young people which numbered 28 people as population. The colleting data throught questionnaires with result showed application of Mate discipleship modul was at very influence category, character transfomation which was at influence category, and Mate discipleship influence to character transfomation in young people Beth-El Tabernakel Kristus Alfa Omega Gajahmada Semarang Church was at average category.